The effect of sagittal alignment, coronal balance, and segmental stability on preoperative patient-reported outcomes in patients with degenerative lumbar spondylolisthesis - Dong-Fan Wang; Xiao-Long Chen; Di Han; Chao Kong; Shi-Bao Lu (BMC Surgery, 2023)
Abstract Objective The aim of this study was to investigate the association between spinal alignment and preoperative patient-reported outcomes (PROs) in patients with degenerative lumbar spondylolisthesis (DLS) and to identify the independent risk factors for worse preoperative PROs. Methods In total, 101 patients suffering from DLS were retrospectively studied within a single medical center. Age, sex, height, weight, and body mass index were uniformly recorded. PRO-related indicators include the Oswestry Disability Index (ODI), the Japanese Orthopedic Association’s (JOA) score, and the visual analog scale (VAS) for back and leg pain. Sagittal alignment, coronal balance, and stability of the L4/5 level were evaluated through whole-spine anteroposterior and lateral radiographs and dynamic lumbar X-ray. Results Increasing age (P = 0.005), higher sagittal vertical axis (SVA) (P < 0.001), and global coronal imbalance (GCI) (P = 0.023) were independent risk factors for higher ODI. Patients with GCI had lower JOA scores (P = 0.001) than those with balanced coronal alignment. Unstable spondylolisthesis (P < 0.001) and GCI (P = 0.009) were two vital predictors of VAS-back pain. Increasing age (P = 0.031), local coronal imbalance (LCI) (P < 0.001), and GCI (P < 0.001) were associated with higher VAS-leg pain. Moreover, patients with coronal imbalance also exhibited significant sagittal malalignment based on the subgroup analysis. Conclusion DLS patients with higher SVA, unstable spondylolistheses, a combination of LCI/GCI, or increasing age were predisposed to have more severe subjective symptoms before surgery.